Reorienting the Role of Students as Subjects of Learning: A Conceptual Analysis Based on Student Agency and Ta'dib - Irfan Maulana Adnan; Fikri Fathul Aziz; Aulia Nazar; Lutpita Firdatul Jannah; Billy Putra (Lembaga Yasin AlSys, 2026)
Twenty-first-century education requires a transformation from a one-way teaching model toward a learning ecosystem that positions students as active subjects in the learning process. In Islamic secondary schools in Indonesia, the Kurikulum Merdeka policy has encouraged flexibility and student-centered learning. However, teacher-centered learning practices remain dominant, so learning initiative, the ability to determine strategies, and self-reflection as the core of student agency are still developing partially and inconsistently. This study aims to examine the misalignment between participatory curriculum design and students’ learning experiences at the classroom level, particularly in relation to the concept of ta’dib as the ethical-epistemic foundation of Islamic education. The discussion shows that ta’dib is often reduced to a set of rules of external compliance, without being accompanied by space for meaningful moral reflection. This condition indicates value disorientation and structural misalignment in educational practice, which affects the instability of students’ subjectivity and moral agency. The conclusion of this study emphasizes the importance of reorienting Islamic learning so that it not only stresses formal compliance but also develops students’ reflective awareness, moral responsibility, and active participation as part of holistic education.